Aid, Policy and Peace : Reducing the Risks of Civil Conflict - Bannon, Ian (World Bank, Washington, DC, 2012)
This note, summarizing recent research by Paul Collier and Anke Hoeffler, presents a theoretical and empirical analysis of the effects of economic policy and aid on the risks of conflict. It finds that aid and policy do not have direct effects on conflict risk. However, both directly affect growth and dependence on primary commodity exports, and these in turn affect conflict risk. Simulating the effect of a package of policy reform and increased aid on the average aid recipient country, it finds that if sustained for five years the risk of conflict is reduced by nearly 30%.